Nanotechnology for wireless gas sensor - Hamidon, Mohd Nizar (2017)
Gas sensor are increasingly being employed, not only in industrial settings and also in every aspect of human life, where they are telling something about their environment by bridging them with the electronic world. Sensors are used to gather a wealth of information from the process that can improve operational efficiency and product quality which involving a mass of data that need to be analysis especially with the merging of the Internet of Things (IoT). They included with new features such as communication capability and on-board diagnostics. Meanwhile, leading edge research in sensors has been propelled by the advancements made in fabrication, signal processing and nanotechnology in the last decade. With these the scientific world is now on the verge of delivering sensors with radically new capabilities for the human societies. This talk deals with the future trend in sensor technology especially for wireless gas sensor and several researches works in Universiti Putra Malaysia related with them.